Knowledge regarding scrub typhus among nurses at a teaching hospital in Chitwan - Gautam, Pradeepti; Poudyal, Sunita (Journal of Chitwan Medical College, 2017)
The incidence of scrub typhus is increasing steadily with evidence of multi organ dysfunction. Lack of knowledge among health personnel may lead to under diagnosis and improper treatment of scrub typhus. Hence, this study was undertaken to find out the knowledge regarding scrub typhus among nurses. A descriptive cross-sectional research design was used and a total 107 nurses were selected by probability, simple random sampling through lottery method. Data was collected using semi-structured self administered questionnaire. Obtained data was entered in IBM SPSS version 20.0 for window. Descriptive statistics was used for categorical and continuous variables and x2 test was used to find out the association between level of knowledge and selected variables. The result of the study shows that 58.9% of the respondents were in the age group of 20-23 years, 69.2% had completed PCL nursing, 50.5% had less than 2 years of work experience, and 64.5% had been working in critical area. More than half (55.1%) of the nurses had adequate level of knowledge regarding scrub typhus and the level of knowledge regarding scrub typhus was influenced by professional qualification (p=0.001) and self directed learning (p=0.010). The study concluded that nearly half of the nurses have inadequate knowledge regarding scrub typhus. Therefore, in-service education is needed for the nurses to build up their capacity for the proper management and prevention of disease.